E Eosinophils have an essential role in cardiac repair following myocardial infarction. (5th June 2017) - Toor, Iqbal S; Rückerl, Dominik; Thomson, Adrian; Tang, Kare; Newby, David E; Rossi, Adriano G; Allen, Judith E; Grey, Gillian A
Abstract : Background: Low peripheral blood eosinophil count is associated with increased risk of mortality in ischaemic heart disease patients. Eosinophils contain preformed IL-4 within their cytoplasmic granules, which promotes an anti-inflammatory response and is associated with tissue repair. Whether eosinophils are recruited to the infarct zone and have a role in regulating infarct repair is currently unknown. Purpose: This study sought to investigate the role of eosinophils in infarct healing. Methods: MI was induced by permanent coronary artery ligation in 12–15 week-old male wild-type (WT) BALB/c and eosinophil deficient ΔdblGATA mice. Cardiac function was assessed 7 days later by high-resolution ultrasound. A cohort of 732 patients undergoing emergency percutaneous coronary intervention for ST-elevation myocardial infarction (STEMI) were followed up for 6 month all-cause mortality. Results: Histochemical staining (Siglec F+) and single cell digestion of infarcted WT BALB/c hearts revealed significant recruitment of (CD11b+SiglecF+Ly6Gint) eosinophils to the infarcted heart. Genetic eosinophil deficiency in ΔdblGATA mice led to greater left ventricular dilatation relative to WT BALB/c mice and worse cardiac function at Day 7 post-MI. Patients with a low eosinophil count at Day 1 following STEMI had an increased risk of 6 month all-cause mortality. On multivariate analysis the hazard ratio of all-cause mortality in the first tertile of peripheral blood eosinophil count at Day 1 post-MI was 6.97 [2.18–22.32] compared to the highest tertile (p=0.001). Treatment with IL-4 complexes was able to rescue the adverse cardiac remodelling of eosinophil-deficient ΔdblGATA mice. Expression of plod2, lox and Fmod genes, which are involved in post-translational collagen modification, were increased in hearts from ΔdblGATA mice. This was accompanied with longer infarct length in ΔdblGATA mice compared to WT BALB/c mice (p=0.01). Conclusions: This study provides the first evidence for an essential role of eosinophils in the tissue repair response following MI, through regulating genes associated with connective tissue biogenesis. Patients with a low eosinophil post-MI may benefit from IL-4 therapy to improve outcome.